Seeking challenge in the career - Baugh, S. Gayle; Sullivan, Sherry E., 1961- (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
The Research in Careers series is designed in five volumes to provide scholars a unique forum to examine careers issues in today's changing, global workplace. What makes this series unique is that the volumes are connected by the use of Mainiero and Sullivan's (2006) Kaleidoscope Career Model (KCM) as the organizing framework and the theme underlying the volumes.In Volume 4 of the Research in Careers series, the authors explore the influence of challenge on career development and career outcomes. The contributors investigate career challenge in different national contexts (e.g., India) and in different career fields (e.g., entrepreneurship, nursing) and for different groups (nurses, Millennials). The outcomes studied include career satisfaction, leadership skills, and occupational expertise. Finally, negative effects of challenge are suggested.
Keywords: Career development.; Job satisfaction.; Job hunting.; Generation Y -- Employment.; Business & Economics -- Careers -- Career Advancement & Professional Development.; Management: leadership and motivation.; Advice on careers and achieving success.; elektronické knihy; electronic books